Wear-resistant lubricating and toughening ZTA (Zirconium Titanate) composite ceramic material and preparation method thereof

By adding yttrium oxide to stabilize zirconia and tungsten or molybdenum metal powder to the alumina ceramic material, and using wet ball milling and discharge plasma sintering technology, ZTA composite ceramic materials with higher hardness, toughness, wear resistance and low friction coefficient are prepared, solving the problem of insufficient performance of existing ceramic materials in special environments.

CN119551972APending Publication Date: 2025-03-04HUBEI POLYTECHNIC UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411743354.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-30
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

Existing alumina ceramic materials are difficult to meet the comprehensive performance requirements of high hardness, toughness, wear resistance and low friction coefficient in certain special environments.

Method used

ZTA composite ceramic materials are prepared by wet ball mill mixing and discharge plasma sintering technology using a combination of alumina powder, yttria stable zirconia powder and tungsten or molybdenum metal powder.

Benefits of technology

It significantly improves the hardness, fracture toughness, friction coefficient and wear rate of ZTA ceramic materials, meeting more stringent application needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119551972A_ABST
    Figure CN119551972A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of ceramic-based composite materials, in particular to a wear-resistant lubricating and toughening ZTA composite ceramic material and a preparation method thereof. The preparation method specifically comprises the following steps: a, respectively carrying out water immersion, centrifugation and drying on 100-200nm aluminum oxide powder and 1-2mu m yttrium oxide stabilized zirconium oxide powder to finish raw material pretreatment; b, adding a ball-milling medium alcohol into the aluminum oxide powder, the yttria-stabilized zirconia powder and auxiliary metal powder which are pretreated in the step a, and performing long-time wet ball-milling mixing; c, the powder obtained after ball milling and mixing in the step b is dried for 12-24 h at the temperature of 100-120 DEG C; and d, putting the powder dried in the step c into a discharge plasma sintering furnace, and sintering to obtain the ZTA composite ceramic material. The ZTA multiphase ceramic material has the advantages of short sintering time, energy consumption reduction, high fracture toughness, enhanced wear resistance, friction coefficient reduction and high hardness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic-based composite materials, and in particular to a wear-resistant, lubricating and toughened ZTA composite ceramic material and a preparation method thereof. Background Art

[0002] Compared with metal materials, ceramic materials have the characteristics of high hardness, wear resistance, corrosion resistance, high temperature resistance, and high electrical insulation. They are widely used in aerospace, device parts, new energy equipment industry, biomedicine and other fields. Due to the crystal structure characteristics of ceramic materials themselves, ceramic chemical bonds are mostly ionic bonds and covalent bonds. There is a lack of slip system inside ceramic materials, the energy required for dislocation is high, plastic deformation is difficult, and the toughness is poor. Compared with metal materials, ceramic materials are highly brittle and are prone to brittle fracture under on-site forces. The brittleness of ceramics has become an important reason restricting its development.

[0003] In addition, wear has always been one of the important reasons for material and energy loss in the industrial field, accounting for about 1 / 3 to 1 / 2 of the total energy consumption. For example, wear-resistant ceramic pipes are a common wear-resistant device, usually used to transport high-concentration and large-particle media. Compared with traditional steel pipes, wear-resistant ceramic pipes can greatly reduce energy consumption and maintenance costs in the production process, and also extend the service life of equipment, because ceramics have many excellent characteristics such as friction resistance, high insulation, high hardness and corrosion resistance. For such applications, ceramics are required to have the comprehensive properties of high hardness, toughness, wear resistance and low friction coefficient.

[0004] With the development of industries such as petroleum, aerospace, mechanical electronics, and artificial joints, ordinary alumina ceramic materials can no longer meet the needs of some special environments, and ceramic materials with better performance should be developed. Later, after continuous efforts by researchers, a new type of composite strong and tough ceramic material was obtained with Al2O3 as the matrix and ZrO2 particles added as the toughening phase. Zirconia phase change toughened alumina composite ceramic (ZTA) combines the dual advantages of zirconium oxide and alumina, bringing significant breakthroughs in the field of ceramic applications. Compared with single-component ceramic materials, this composite ceramic material exhibits more outstanding mechanical properties, not only enhancing the toughness and hardness of the ceramic. Although zirconium oxide phase change toughening is introduced on the basis of alumina ceramics, the strengthening effect of this single phase is limited, and the friction coefficient is high, which cannot meet the performance requirements of some special industries. For example, ceramic tool materials must have excellent heat resistance, wear resistance, chemical stability and low friction coefficient, and fracture toughness, wear resistance and lubrication performance need to be further improved, which is urgently needed.

[0005] The above contents are only used to assist in understanding the technical solution of the present invention, and do not constitute an admission that the above contents are the closest prior art. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a wear-resistant, lubricating and toughened ZTA composite ceramic material and a preparation method thereof.

[0007] To achieve the above-mentioned purpose, the technical solution of the present invention is implemented as follows: a wear-resistant, lubricating and toughened ZTA composite ceramic material and a preparation method thereof, comprising: alumina powder, yttria-stabilized zirconia powder, tungsten metal powder or molybdenum metal powder; by weight: the alumina powder accounts for 75-80% of the total mass of the powder; the yttria-stabilized zirconia powder accounts for 15-25% of the total mass of the powder; the tungsten metal powder or molybdenum metal powder accounts for 1-10% of the total mass of the total powder.

[0008] Preferably, the method specifically comprises the following steps:

[0009] a. Soaking alumina powder and yttria-stabilized zirconia powder in water, centrifuging and drying them respectively to complete the raw material pretreatment;

[0010] b. Adding alcohol to the alumina powder, yttria-stabilized zirconia powder (5YSZ) and tungsten metal powder or molybdenum metal powder pretreated in step a, and performing wet ball milling to mix;

[0011] c. Drying the powder obtained by ball milling in step b at a temperature of 100 to 120° C. for 12 to 24 hours;

[0012] d. Place the powder after vacuum drying in step c into a spark plasma sintering furnace for sintering to obtain a ZTA composite ceramic material.

[0013] Preferably, the sintering in step d is divided into early, middle and late stages, and the specific sintering process is:

[0014] Early stage of sintering: the temperature is raised from room temperature to 500-700°C, the heating rate is 50-100°C / min, and the sintering pressure is 0MPa;

[0015] Mid-sintering: The temperature continues to rise to 1200°C on the basis of the early sintering temperature, with a heating rate of 100-150°C / min. During the heating process, the sintering pressure gradually rises to 20-40MPa. After the heating is completed, the temperature is kept for 3-5 minutes. During the heating, the sintering pressure gradually increases to 30-60MPa.

[0016] Late sintering: After the insulation in the middle stage of sintering is completed, the temperature is raised to 1300-1400°C based on the temperature in the middle stage of sintering, with a heating rate of 50-100°C / min and insulation for 3-5 minutes. During this process, the pressure is maintained consistent with the pressure in the middle stage of sintering; after the insulation in the late stage of sintering is completed, sintering is completed, heating and pressurization are stopped, and the temperature drops to room temperature with the furnace to end sintering.

[0017] Preferably, the particle size of the tungsten metal powder or molybdenum metal powder in step b is 1 to 2 μm.

[0018] Preferably, the tungsten metal powder or molybdenum metal powder accounts for 1-5% of the total mass of the total powder.

[0019] Preferably, the particle size of the yttria-stabilized zirconia (5YSZ) powder is 1 to 2 μm; and the particle size of the alumina powder is 100 to 200 nm.

[0020] Preferably, in step b, the ball-to-material ratio of the ball milling is 8:1, the ball milling speed is 300 r / min, and the ball milling time is 40 h; the ball milling medium is anhydrous ethanol, and the amount of anhydrous ethanol added is enough to cover the spheres.

[0021] Preferably, the hardness of the ZTA composite ceramic material obtained in step d is 16.1 to 17.5 GPa; the fracture toughness of the ZTA composite ceramic material is 6.0 to 7.1 MPa·m 1 / 2 The friction coefficient of ZTA composite ceramic material is 0.18-0.19; the wear rate of ZTA composite ceramic material is 1.1-3.4×10 -7 mm 3 / (N·m).

[0022] The beneficial effects of the present invention are embodied in:

[0023] (1) The present invention uses 100-200nm alumina and 1-2μm yttria-stabilized zirconia (5YSZ) powders, and mixes them evenly in an anhydrous ethanol medium for 40 hours. During the sintering process, small-sized Al2O3 particles will wrap large-sized ZrO2 to form an internal crystal structure, achieving a good toughening effect. Agglomeration occurs between the two, and ZTA ceramics with better mechanical properties can be obtained.

[0024] (2) The present invention uses monoclinic yttria-stabilized zirconia powder (5YSZ) as the raw material for ZTA ceramics; first, when passing the phase transition temperature, the monoclinic ZrO2 is converted into a tetragonal crystal structure, and the volume shrinkage causes cracks in the sintered product. The added yttria can increase the temperature range in which ZrO2 can stably exist in the tetragonal phase. Secondly, during the spark plasma sintering process, the monoclinic m-ZrO2 will transform into the metastable tetragonal t-ZrO2. t-ZrO2 absorbs strain energy and undergoes significant volume expansion, which will apply compressive stress to the cracks. This effect requires more energy for the crack to expand, thereby enhancing the toughness of the ZTA ceramics.

[0025] (3) Adding soft metal phases Mo or W, a thin lubricating friction film rich in molybdenum oxide / tungsten oxide is formed on the wear surface. Adhesion as the main wear mechanism can reduce the number of hard abrasive particles at the friction interface during the wear process, reduce wear losses, and reduce the friction coefficient. In addition, the plastic deformation of the second phases of metal Mo and W can relieve stress concentration, change the crack propagation path, disperse the energy required for the main crack to propagate, increase the energy consumption of crack propagation, and improve the toughness of ZTA ceramics.

[0026] (4) The spark plasma sintering technology (SPS) used has higher thermal efficiency. The plasma discharge heats up quickly and can effectively inhibit the growth of grains during the heating process. The plasma used directly heats the sample, and the energy utilization efficiency is higher than that of traditional furnace heating. The sintering process of the present invention only takes half an hour to complete the entire sintering process. At the same time, the sintering temperature is 1300-1400℃ to obtain high-quality and high-performance ZTA ceramic materials.

[0027] (5) The ZTA composite ceramic material obtained by the method provided by the present invention has improvements in hardness, fracture toughness, friction coefficient and wear rate compared with the existing zirconia phase change toughened alumina composite ceramics, which expands the application scenarios of ceramics. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The SEM images of the ZTA-W and ZTA-Mo mixed powders in Examples 1 and 2 of the present invention;

[0029] Figure 2 is the XRD pattern of the ZTA-Mo ceramic block in Example 2 of the present invention;

[0030] Figure 3 The surface morphology and element distribution diagram of the ZTA-W ceramic block in Example 1 of the present invention;

[0031] Figure 4 This is an indentation morphology of the ZTA-W ceramic block in Example 1 of the present invention under a 5Kg Vickers hardness tester indenter;

[0032] Figure 5 Graph showing the coefficient of friction of Examples 1, 2 and 3 of the present invention. DETAILED DESCRIPTION

[0033] The technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention and the comparative examples. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. In the absence of conflict, the embodiments in this application and the features in the embodiments can be combined with each other. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the scope of protection of the present invention.

[0034] Example 1

[0035] A method for preparing a wear-resistant, lubricating and toughened ZTA composite ceramic material, specifically comprising the following steps:

[0036] a. Soaking alumina powder and yttria-stabilized zirconia (5YSZ) powder in water, centrifuging and drying them respectively to complete the raw material pretreatment;

[0037] b. Add alcohol to the alumina powder, yttria-stabilized zirconia powder (5YSZ) and auxiliary metal powder pretreated in step a, and then perform wet ball milling. The ball-to-material ratio of the ball milling is 8:1, the ball milling speed is 300 r / min, and the ball milling time is 40 h; the ball milling medium is anhydrous ethanol, and the amount of anhydrous ethanol added is enough to cover the balls.

[0038] The auxiliary metal powder is molybdenum metal powder, and the particle size of the molybdenum metal powder is 1-2μm. By weight: the alumina powder accounts for 75% of the total mass of the powder. The yttria-stabilized zirconia powder accounts for 20% of the total mass of the powder; the molybdenum metal powder accounts for 5% of the total mass of the total powder. The purity of the molybdenum metal powder is greater than 99.99%, and the purity of the alumina powder and the yttria-stabilized zirconia powder is greater than 99.99%; the particle size of the alumina powder is 100-200nm.

[0039] c. Dry the powder obtained by ball milling in step b at 120° C. for 20 h.

[0040] d. Place the powder after vacuum drying in step c into a spark plasma sintering furnace for sintering to obtain a ZTA composite ceramic material.

[0041] Step d: Sintering is divided into early, middle and late stages. The specific sintering process is as follows:

[0042] Early stage of sintering: the temperature is raised from room temperature to 600°C, the heating rate is 50°C / min, and the sintering pressure is 0MPa;

[0043] Mid-sintering: The temperature continues to rise to 1200°C on the basis of the early sintering temperature, with a heating rate of 100°C / min. During the heating process, the sintering pressure gradually rises to 40MPa within 5 minutes. After the heating is completed, the temperature is kept for 5 minutes, and the sintering pressure increases to 60MPa during the heating.

[0044] Late sintering: After the insulation in the middle stage of sintering is completed, the temperature is raised to 1300℃ based on the temperature in the middle stage of sintering, with a heating rate of 50℃ / min and insulation for 5min. During this process, the pressure is maintained at 60MPa. After the insulation in the late stage of sintering is completed, sintering is completed, heating and pressurizing are stopped, and the temperature is cooled to room temperature with the furnace to end sintering.

[0045] The hardness of the obtained ZTA composite ceramic material is 16.1GPa; the fracture toughness of the ZTA composite ceramic material is 6.9MPa·m 1 / 2 ; The friction coefficient of ZTA composite ceramic material is 0.18; The wear rate of ZTA composite ceramic material is 3.4×10 - 7 mm 3 / (N·m).

[0046] Example 2

[0047] A method for preparing a wear-resistant, lubricating and toughened ZTA composite ceramic material, specifically comprising the following steps:

[0048] a. Soaking alumina powder and yttria-stabilized zirconia (5YSZ) powder in water, centrifuging and drying them respectively to complete the raw material pretreatment;

[0049] b. Add alcohol to the alumina powder, yttria-stabilized zirconia powder (5YSZ) and auxiliary metal powder pretreated in step a, and then perform wet ball milling; the ball-to-material ratio of the ball milling is 8:1, the ball milling speed is 300 r / min, and the ball milling time is 40 h; the ball milling medium is anhydrous ethanol, and the amount of anhydrous ethanol added is enough to cover the balls.

[0050] The auxiliary metal powder is tungsten metal powder; and the particle size of the tungsten metal powder is 1-2μm. By weight: alumina powder accounts for 75% of the total mass of the powder; yttria-stabilized zirconia powder accounts for 20% of the total mass of the powder; tungsten metal powder accounts for 5% of the total mass of the total powder. The purity of tungsten metal powder is greater than 99.99%, and the purity of alumina powder and yttria-stabilized zirconia powder is greater than 99.99%; the particle size of alumina powder is 100-200nm.

[0051] c. Dry the powder obtained by ball milling in step b at 100° C. for 24 h.

[0052] d. Place the powder after vacuum drying in step c into a spark plasma sintering furnace for sintering to obtain a ZTA composite ceramic material.

[0053] Step d: Sintering is divided into early, middle and late stages. The specific sintering process is as follows:

[0054] Early stage of sintering: the temperature is raised from room temperature to 600°C, the heating rate is 100°C / min, and the sintering pressure is 0MPa;

[0055] Mid-sintering: The temperature continues to rise to 1200°C on the basis of the early sintering temperature, with a heating rate of 100°C / min. During the heating process, the sintering pressure gradually rises to 30MPa within 5 minutes. After the heating is completed, the temperature is kept for 5 minutes, and the sintering pressure increases to 60MPa during the heating.

[0056] Late sintering: After the insulation in the middle stage of sintering is completed, the temperature is raised to 1400℃ based on the temperature in the middle stage of sintering, with a heating rate of 50℃ / min and insulation for 5 minutes. During this process, the pressure is maintained consistent with the pressure in the middle stage of sintering; After the insulation in the late stage of sintering is completed, sintering is completed, heating and pressurization are stopped, and the temperature is cooled to room temperature with the furnace to end sintering.

[0057] The hardness of the obtained ZTA composite ceramic material is 17.5GPa; the fracture toughness of the ZTA composite ceramic material is 7.1MPa·m 1 / 2 The friction coefficient of ZTA composite ceramic material is 0.19; the wear rate of ZTA composite ceramic material is 1.1×10 - 7 mm 3 / (N·m).

[0058] Embodiment 3:

[0059] A method for preparing a wear-resistant, lubricating and toughened ZTA composite ceramic material, specifically comprising the following steps:

[0060] a. Soaking alumina powder and yttria-stabilized zirconia (5YSZ) powder in water, centrifuging and drying them respectively to complete the raw material pretreatment;

[0061] b. Add alcohol to the alumina powder and yttria-stabilized zirconia powder (5YSZ) pretreated in step a, and perform wet ball milling; the ball-to-material ratio of the ball milling is 8:1, the ball milling speed is 300 r / min, and the ball milling time is 40 h; the ball milling medium is anhydrous ethanol, and the amount of anhydrous ethanol added is enough to cover the balls.

[0062] By weight: alumina powder accounts for 80% of the total mass of the powder; yttria-stabilized zirconia powder accounts for 20% of the total mass of the powder; and the purity of alumina powder and yttria-stabilized zirconia powder is greater than 99.99%; the particle size of the alumina powder is 100-200nm.

[0063] c. Dry the powder obtained by ball milling in step b at 100° C. for 24 h.

[0064] d. Place the powder after vacuum drying in step c into a spark plasma sintering furnace for sintering to obtain a ZTA ceramic material. The sintering in step d is divided into the early, middle and late stages. The specific sintering process is as follows:

[0065] Early stage of sintering: the temperature is raised from room temperature to 600°C, the heating rate is 50°C / min, and the sintering pressure is 0MPa;

[0066] Mid-sintering: The temperature continues to rise to 1200°C on the basis of the early sintering temperature, with a heating rate of 100°C / min. During the heating process, the sintering pressure gradually rises to 40MPa within 5 minutes. After the heating is completed, the temperature is kept for 5 minutes, and the sintering pressure increases to 60MPa during the heating.

[0067] Late sintering: After the insulation in the middle stage of sintering is completed, the temperature is raised to 1300℃ based on the temperature in the middle stage of sintering, with a heating rate of 50℃ / min and insulation for 5 minutes. During this process, the pressure is maintained consistent with the pressure in the middle stage of sintering; After the insulation in the late stage of sintering is completed, sintering is completed, heating and pressurization are stopped, and the temperature drops to room temperature with the furnace to end sintering.

[0068] The hardness of the obtained ZTA ceramic material is 18.2GPa, and the fracture toughness of the ZTA ceramic material is 6.0MPa·m 1 / 2 ; The friction coefficient of ZTA ceramic material is 0.58; The wear rate of ZTA ceramic material is 16.2×10 -7 mm 3 / (N·m).

[0069] From the comparison between the above comparative examples and the embodiments, it can be seen that:

[0070] Figure 1 The morphology of the ZTA ceramic and metal mixed powder prepared in Example 1 and Example 2 of the present invention; Figure 1 It can be seen that alumina powder with a particle size of 100-200 nm covers zirconium oxide, and the mixing uniformity is good.

[0071] Figure 2 is the XRD diagram of the ZTA-Mo ceramic block in Example 2 of the present invention; Figure 2 It can be seen that a high volume fraction of tetragonal zirconia is obtained after sintering, and the diffraction peak of metal Mo can be observed.

[0072] Figure 3 is the surface morphology and element distribution diagram of the ZTA-W ceramic block in Example 1 of the present invention; Figure 3 It can be seen that the surface of the ceramic block is smooth without obvious pores, the O, AI, Zr, and Y elements are evenly distributed, and there is a precipitation phase of metal W.

[0073] Figure 4 This is an indentation morphology of the ZTA-W ceramic block in Example 1 of the present invention under a 5Kg Vickers hardness tester indenter; the fracture toughness of the example is judged by the crack extension.

[0074] Figure 5 The friction coefficient curves of Examples 1, 2, and 3 of the present invention are as follows; from the comparison between the curves and the performance of the examples, it can be seen that adding an appropriate amount of metal Mo and W is beneficial to refining the grain size, enhancing the fracture toughness, significantly improving the wear resistance (the wear rate is reduced by one order of magnitude) and reducing the friction coefficient (from 0.58 to 0.18-0.19).

[0075] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A wear-resistant, lubricating and toughened ZTA composite ceramic material, characterized in that: include: Alumina powder, yttria-stabilized zirconia powder, tungsten metal powder or molybdenum metal powder; by weight: the alumina powder accounts for 75-80% of the total mass of the powder; the yttria-stabilized zirconia powder accounts for 15-25% of the total mass of the powder; the tungsten metal powder or molybdenum metal powder accounts for 1-10% of the total mass of the powder.

2. The method for preparing a wear-resistant, lubricating and toughened ZTA composite ceramic material according to claim 1, characterized in that: The specific steps include: a. Soaking alumina powder and yttria-stabilized zirconia powder in water, centrifuging and drying them respectively to complete the raw material pretreatment; b. Adding alcohol to the alumina powder, yttria-stabilized zirconia powder, and tungsten metal powder or molybdenum metal powder pretreated in step a, and performing wet ball milling for 20 to 40 hours; c. Drying the powder obtained by ball milling in step b at a temperature of 100 to 120° C. for 12 to 24 hours; d. Place the dried powder in step c into a spark plasma sintering furnace for sintering to obtain a ZTA composite ceramic material.

3. The method for preparing a wear-resistant, lubricating and toughened ZTA composite ceramic material according to claim 2, characterized in that: Step d: Sintering is divided into early, middle and late stages. The specific sintering process is as follows: Early stage of sintering: the temperature is raised from room temperature to 500-700°C, the heating rate is 50-100°C / min, and the sintering pressure is 0MPa; Mid-sintering: The temperature continues to rise to 1200°C on the basis of the early sintering temperature, with a heating rate of 100-150°C / min. During the heating process, the sintering pressure rises to 20-40MPa. After the heating is completed, the temperature is kept for 3-5 minutes. During the heating, the sintering pressure increases to 30-60MPa. Late sintering: After the mid-term insulation of sintering is completed, the temperature is raised to 1300-1400°C based on the mid-term temperature of sintering, with a heating rate of 50-100°C / min, and the temperature is kept for 3-5 minutes. During this process, the pressure continues to be maintained consistent with the pressure in the mid-term of sintering; after the late sintering insulation is completed, sintering is completed, heating and pressurization are stopped, and the temperature drops to room temperature with the furnace to end sintering.

4. The method for preparing a wear-resistant, lubricating and toughened ZTA composite ceramic material according to claim 2, characterized in that: The particle size of the tungsten metal powder or molybdenum metal powder in step b is 1 to 2 μm.

5. The method for preparing a wear-resistant, lubricating and toughened ZTA composite ceramic material according to claim 2, characterized in that: The zirconium oxide in the ZTA ceramic described in step a comes from yttria-stabilized zirconia powder; and the particle size of the yttria-stabilized zirconia powder is 1 to 2 μm.

6. The method for preparing a wear-resistant, lubricating and toughened ZTA composite ceramic material according to claim 5, characterized in that: The tungsten metal powder or molybdenum metal powder accounts for 1-10% of the total mass of the total powder.

7. The method for preparing a wear-resistant, lubricating and toughened ZTA composite ceramic material according to claim 6, characterized in that: The particle size of the alumina powder is 100-200 nm.

8. The method for preparing a wear-resistant, lubricating and toughened ZTA composite ceramic material according to claim 7, characterized in that: In step b, the ball-to-material ratio of ball milling is 8:1, the ball milling speed is 300 r / min, and the ball milling time is 20 to 40 hours; the ball milling medium is anhydrous ethanol, and the amount of anhydrous ethanol added is enough to cover the spheres.

9. The method for preparing a wear-resistant, lubricating and toughened ZTA composite ceramic material according to claim 2, characterized in that: The hardness of the ZTA composite ceramic material obtained in step d is 16.1-17.5 GPa; the fracture toughness of the ZTA composite ceramic material is 6.0-7.1 MPa·m 1 / 2 The friction coefficient of ZTA composite ceramic material is 0.18-0.19; the wear rate of ZTA composite ceramic material is 1.1-3.4×10 -7 mm 3 / (N·m).

Citation Information

Cited By

  • A low-cost chemical method for preparing high-toughness ZTA ceramics

    CN122853867A